A case of primary immunodeficiency: hyper IgM syndrome - Fadnis, Madhura P.; Shamkuwar, Pratibha B. (International Journal of Contemporary Pediatrics, 2019)
Hyper IgM syndrome are group to disorders characterized by elevated serum level of IgM and low or absent serum levels of IgG, IgA and IgE the mechanism of HIGM is immunoglobulin Class-Switch Recombination (CSR) failure and Somatic Hyper Mutation (SHM). This diagnosis should be considered in any patient presenting with hypogammaglobulinemia, with low or absent IgG and IgA and normal or elevated IgM level. In the present case report, this was a 6-year-old male child who had history of recurrent respiratory tract infections who presented with otitis media and persistent fever spikes. Immunoglobulin studies revealed a pattern consistent with hyper IgM.